2020
DOI: 10.1186/s12913-019-4794-6
|View full text |Cite
|
Sign up to set email alerts
|

Till death do us part: the effect of marital status on health care utilization and costs at end-of-life. A register study on all colorectal cancer decedents in Norway between 2009 and 2013

Abstract: Background: Economic analyses of end-of-life care often focus on single aspects of care in selected cohorts leading to limited knowledge on the total level of care required to patients at their end-of-life. We aim at describing the living situation and full range of health care provided to patients at their end-of-life, including how informal care affects formal health care provision, using the case of colorectal cancer. Methods: All colorectal cancer decedents between 2009 and 2013 in Norway (n = 7695) were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
6
16
1
Order By: Relevance
“…Marital status, coping with the diagnosis, dealing with pain, and a reduced willingness among men to seek healthcare might all play a part 21 . Similar findings have been reported in colorectal cancer, where a recent Scandinavian study 22 noted that married patients spent 30 days less in hospital, and used less home- and community-based care in an end-of-life setting. A study from 2019 found that married patients with advanced cancer were less likely to have potentially avoidable readmissions 23 .…”
Section: Discussionsupporting
confidence: 83%
“…Marital status, coping with the diagnosis, dealing with pain, and a reduced willingness among men to seek healthcare might all play a part 21 . Similar findings have been reported in colorectal cancer, where a recent Scandinavian study 22 noted that married patients spent 30 days less in hospital, and used less home- and community-based care in an end-of-life setting. A study from 2019 found that married patients with advanced cancer were less likely to have potentially avoidable readmissions 23 .…”
Section: Discussionsupporting
confidence: 83%
“…The study population is further divided into the married and widowed group. Moreover, as the sex aspect having a material impact on the health service utilisation, this study further used men and women elderly separately by their marital Status [5,22]…”
Section: Study Samplementioning
confidence: 99%
“…The marital status and its association with health status has been at the forefront of investigation for a long time but with insu cient explanations. Previous studies have demonstrated that with the change in marital status, individuals experience differential health status and health care utilisation [1][2][3][4][5]. Studies have reported that nonmarried individuals are perhaps more deprived in terms of social and economic status compared to their counterparts, married individuals [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations